PERAN KELUARGA TERHADAP LANSIA di PUSKESMAS REJOSARI - Liva Maita (Universitas Nahdlatul Ulama Surabaya, 2017)
In Indonesia the attention to the elderly population increases mainly due to the number that tends to increase rapidly. In 2010, the number of elderly residents living in urban areas was 12,380,321 people (9.58%), and those living in rural areas of 15.612.232 people (9.97%). There is a considerable difference between the elderly in the city and in the village. This difference can be due to the migration patterns of young people to the city and their old age prefer to their village, and villagers have a greater life expectancy because they do not breathe polluted air, do not often face the things that make them more stressful, tentramnya rather than the days of stress, and also because the food consumed is not contaminated with pesticides, thus making them not susceptible to disease. General Purpose Knowledge of family role to health of elderly at Rejosari Health Center Pekanbaru year 2013. Type of research was descriptive. Sample in this study as many as 94 elderly who taken mengguankan purposive sampling technique, the data were analyzed univariat. The result of the research showed the role of family in the health examination of the elderly with good category (88,30%), the role of family in the fulfillment of good nutrition of elderly with good category (98,94%), family role in meeting the needs of rest and sleep of elderly with good category (91, 94%) and the role of family with good category (95%). It is expected that the PHC to improve the Elderly Health Program in PHC through health examination and gymnastics elderly every week.